The Impact of Ownership and Financial Stability on Bank Liquidity Creation - Sudarto, Sudarto; Adawiyah, Wiwiek Rabiatul; Najmudin, Najmudin; Jati, Dian Purnomo (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
Employing a descriptive approach, this study intends to investigate the causal relationship between financial stability and liquidity creation and the effects of foreign ownership, local ownership, and financial stability on liquidity creation. The research sample included 35 banks listed on the Indonesia Stock Exchange based on a purposive sampling technique (non-random sampling) and the observation period between 2013 and 2020 utilizing quarterly data. According to the Granger causality test results, there is no reciprocal relationship between the creation of liquidity and financial stability. This indicates that the research variables avoid endogeneity problems. Using static panel data analysis, we discovered that neither foreign ownership nor financial stability has any impact on the creation of bank liquidity; however, the interaction between foreign ownership and financial stability has a significant positive impact, suggesting that the interaction between the two could become stronger. The asset-side liquidity creation component is the only one that plays this role. Domestic ownership favors liquidity creation, but there is less of an effect when ownership and financial stability are combined. When the creation of liquidity increases, production activities increase, suggesting that economic activity increases. Thus, these findings are useful for regulators and central banks in making economic and banking policies by considering bank ownership and stability.